Alternative amidation approaches (2021)
Amide bonds play a crucial role in life not only for their function as the backbones of natural peptides and proteins, but also for their presence in a great number of pharmacological compounds, alkaloids, synthetic polymeric materials, supported catalysts, and biocompatible matrices for cell growth. Consequently, the amide bond is not only one of the most common structural motifs in nature, but also one of the most important functional groups in organic chemistry due to their high stability, polarity, and their conformational diversity. In relation with pharmaceutical field, amides are found at least once as a structural core not only in two-thirds of all drugs candidates, but also in a quarter of all natural and synthetic pharmaceutical drugs currently on the market; therefore, they are an important class of compounds that not only have been exploited in different fields, but also that have had a considerable impact on the industry as highlighted by the various drugs that contain an amide motif. As a result, amide bond formation is one of the most fundamental chemical reactions; hence, traditional amidation methods involve the direct reaction of carboxylic acids with amines, activated carboxylic acid derivatives such as anhydrides or acyl chlorides which react directly with the suitable amines, as well as the generation of activated derivates by the use of stoichiometric amounts of coupling agents. However, those methods are relatively inefficient with large quantities of potentially hazardous and toxic waste products being formed causing a negative environmental impact and difficulties in the purification steps. Consequently, the importance of amide synthesis has increased the interest of the researchers for the development of new and efficient approaches. Among the alternative approaches, methods such as ester amidation, oxidative amidation, and reductive amidation, have been reported which have been advantageous for accessing different classes of amides.